Next-generation sequencing impact on cancer care: applications, challenges, and future directions - Zalis, Mariano; Viana Veloso, Gilson Gabriel; Aguiar Jr., Pedro Nazareth; Gimenes, Nathalia; Reis, Marina Xavier; Matsas, Silvio; Ferreira, Carlos Gil (Frontiers in Genetics, 2024)
Fundamentally precision oncology illustrates the path in which molecular profiling of tumors can illuminate their biological behavior, diversity, and likely outcomes by identifying distinct genetic mutations, protein levels, and other biomarkers that underpin cancer progression. Next generation sequencing became an indispensable diagnostic tool for diagnosis and treatment guidance in current clinical practice. Nowadays, tissue analysis benefits from further support through methods like comprehensive genomic profiling and liquid biopsies. However, precision medicine in the field of oncology presents specific hurdles, such as the cost-benefit balance and widespread accessibility, particularly in countries with low-and middle-income. A key issue is how to effectively extend next generation sequencing to all cancer patients, thus empowering treatment decision-making. Concerns also extend to the quality and preservation of tissue samples, as well as the evaluation of health technologies. Moreover, as technology advances, novel NGS assessments are being developed, including the study of Fragmentomics. Therefore, our objective was to delineate the primary uses of next generation sequencing, discussing its' applications, limitations, and prospective paths forward in Oncology.